6×2-14=40

Add 14 to both sides of the equation.

6×2=40+14

Add 40 and 14.

6×2=54

6×2=54

Divide each term in 6×2=54 by 6.

6×26=546

Cancel the common factor of 6.

Cancel the common factor.

6×26=546

Divide x2 by 1.

x2=546

x2=546

Divide 54 by 6.

x2=9

x2=9

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±9

Simplify the right side of the equation.

Rewrite 9 as 32.

x=±32

Pull terms out from under the radical, assuming positive real numbers.

x=±3

x=±3

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=3

Next, use the negative value of the ± to find the second solution.

x=-3

The complete solution is the result of both the positive and negative portions of the solution.

x=3,-3

x=3,-3

x=3,-3

Solve Using the Square Root Property 6x^2-14=40